2002
DOI: 10.1086/342943
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Collimated Outflows in the Proto–Planetary Nebula GL 618

Abstract: We present narrow-band Hα, [S II], and [O I] Hubble Space Telescope images of the young planetary nebula GL 618. This object is a compact, bipolar nebula that is currently undergoing the transition from asymptotic giant branch star to planetary nebula. Our images confirm the presence of at least three highly collimated outflows emanating from the central regions of GL 618. We also detect Hα emission close to the central dust lane and in an extended scattered light halo. The three outflows are occurring simulta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Roughly the same value of t t ($400 yr) is obtained independently from an expanding torus model of the dense inner regions (r t $ 0:75 00 , v t $ 5Y12 km s À1 ) observed in HC 3 N ( Pardo et al 2004). The angle j is for the single jet b in the nomenclature of Trammell & Goodrich (2002), and v j is the H 2 velocity for same jet (Cox et al 2003).…”
Section: A2 Notes On Individual Sourcessupporting
confidence: 52%
“…Roughly the same value of t t ($400 yr) is obtained independently from an expanding torus model of the dense inner regions (r t $ 0:75 00 , v t $ 5Y12 km s À1 ) observed in HC 3 N ( Pardo et al 2004). The angle j is for the single jet b in the nomenclature of Trammell & Goodrich (2002), and v j is the H 2 velocity for same jet (Cox et al 2003).…”
Section: A2 Notes On Individual Sourcessupporting
confidence: 52%
“…CRL 618 is located at a distance of 900 pc (Goodrich 1991). It shows several narrow lobes at different orientations in Hubble Space Telescope (HST) images (Trammell & Goodrich 2002) and belongs to the "multipolar" morphological classification (Sahai et al 2007), perhaps resulting from multiple ejections at different orientations. The general structures of the different lobes are similar and we focus only on the northwestern (W1) lobe, which seems to be better separated from other lobes.…”
Section: Introductionmentioning
confidence: 99%
“…In the bright East lobe the slit position 1 slices diffuse emission to the south of the bright compact nebulosity (see Fig. 2) and several bow-shaped, ripple-like features (Trammell & Goodrich 2002). Slit 2 crosses the East lobe, sampling several bow-shaped structures at the tips of the outflows.…”
Section: Observations and Reductionmentioning
confidence: 97%
“…SSG02 suggested that region A is the outermost parts of the HII region surrounding the star. In addition to the Hα emission detected in the inner regions and the shocked lobes, a faint halo of emission is present in the Hα HST image (Trammell & Goodrich 2002), likely to be Hα emission scattered by dust present in the outer regions of CRL 618.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation